Socio-Spatial Analysis of Deforestation in Soeharto Forest Using Remote Sensing Method - Tri Furi Megawati; Melati Julia Rahma; Bambang Semedi; Aminudin Afandhi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The broader transformation of forested areas into open land is commonly referred to as deforestation. Deforestation poses a significant challenge to forest preservation and environmental sustainability. This study aims to employ remote sensing methods to analyze the spatial patterns of deforestation in the Soeharto Forest. It is complemented by in-depth interview data gathered from individuals engaged in forest exploitation activities. The findings reveal a notable decline in land cover within the Soeharto Forest Park area from 1992 to 2022, resulting in a reduction to 335,994,000,000 m2. Further analysis of the in-depth interview data indicates that forest fringe communities have taken control of 15,536,393.69 m2 of land to fulfill their livelihood and cultivation needs. The decline in land cover will also be more critical because of moving the national capital. The research results also discussed land cover areas using remote sensing. However, social support discusses whether land cover change is caused by land tenure by forest fringe communities and plans to relocate the national capital. Where this is also influenced by the formulation of government policies that have not balanced bee interests of ecology and the social culture ture of the community.